POTENSI Echinodorus palaefolius SEBAGAI AGEN FITOREMEDIASI DALAM MENURUNKAN KADAR LOGAM MANGAN PADA AIR ASAM TAMBANG BATUBARA: POTENSI Echinodorus palaefolius SEBAGAI AGEN FITOREMEDIASI DALAM MENURUNKAN KADAR LOGAM MANGAN PADA AIR ASAM TAMBANG BATUBARA - Chalista Devi Lestari; Shally Yanova; Putra Fernando Mersa (Fakultas Teknik Universitas Hamzanwadi, 2025)
This study examined the potential of water jasmine (Echinodorus palaefolius) in reducing manganese levels in Coal Acid Mine Drainage (AMD) using an artificial wetland system. The study was conducted experimentally with time variations of 0, 3, 6, and 9 days, where the manganese concentration was analyzed using Atomic Absorption Spectrophotometry (AAS). The results showed that the initial manganese concentration of 9.75 mg/L, which exceeded the quality standard of the Minister of Environment Decree No. 113 of 2003 (4 mg/L), decreased significantly to 3.94 mg/L on the 3rd day and reached 1.002 mg/L on the 9th day with an effectiveness of 89.73%. An independent t-test showed a significant difference (p < 0.05) between with and without plants. The BCF value of 7.028 classifies E. palaefolius as a highly effective accumulator, while the TF value of 0.6 indicates the presence of a phytostabilization mechanism. Research has proven that water jasmine is effective as an environmentally friendly solution for coal-fired wastewater management with the ability to neutralize pH from 4.28 to 6.53 and reduce manganese concentrations below quality standards in a short time.